Geraint Ellis, W kierunku zrozumienia uprawnień podmiotów trzecich w planowaniu przestrzennym, , “Environment and Planning A: Economy and Space”2004, vol. 36 (opr. Piotr Szulc) - Szulc, Piotr (Studia Prawa Publicznego, 2020)
Geraint Ellis, Discourses of Objection: Towards an Understanding of Third-party Rights in Planning (W kierunku zrozumienia uprawnień podmiotów trzecich w planowaniu przestrzennym), „Environment and Planning A: Economy and Space” 2004, vol. 36 (opr. Piotr Szulc)